Estimated effect of monofin stiffness on sports performance in marathon swimmers - Bolotin, A.; Bakayev, V.; Dudchenko, P. (Proceedings of the 9th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2021)
The study conducted has confirmed that the techniques and methods for training marathon swimmers in fins, tailoring the monofin stiffness to the individual capabilities of the athletes, play a major role in increasing the efficiency of training for competitions. The athletes can reliably achieve better results in the training process and in competitions. Training sessions with monofin stiffness taken into account have been found to have a higher efficiency. Our studies established that the kinematic characteristics undergo certain changes, some of them rather considerable. Using the monofin with the stiffness corresponding to individual capabilities of marathon swimmers allowed increasing the intracyclic speed of the strongest athletes from 2.53 m/s to 3.01 m/s (at the end of the experiment), i.e., the speed increase amounted to 19%. This is also confirmed by the increased average speed of distance swimming: 3.02 m/s and 3.48 m/s respectively, which is an increase of 17%. The study s howed that successfully training athletes for competitions largely depends on accounting for the individual characteristics of muscular activity in marathon swimmers and the stiffness of the monofin. We have discovered that higher elasticity of an athlete's muscles should correspond to smaller monofin stiffness. The article presents the results of assessing the effect of monofin stiffness on the performance of marathon swimmers.